Evaluating Social Funds : A Cross-Country Analysis of Community Investments - Rawlings, Laura B. (Washington, DC: World Bank, 2013)
The study seeks to answer four questions that summarize the fundamental issues in the international debate about the capacity of social funds to improve beneficiaries' living conditions: o Do social funds reach poor areas and poor households? Do social funds deliver high-quality, sustainable investments? Do social funds affect living standards? How cost-efficient are social funds and the investments they finance, compared with other delivery mechanisms? The findings and lessons from this research reflect a specific moment in the evolution of six social funds and therefore may not fully predict the future impact of current investments. The evaluation assesses subprojects identified and implemented between 1993 and 1999, a period when longer-term objectives-such as increasing access to and utilization of basic services-began to supplant the funds' original emergency mandates. The time period selected allowed enough elapsed time following the implementation of the social fund subprojects to make measurement of impact and sustainability possible. The evaluation does not consider the effects of social fund projects on employment or on income generation-the original objectives of the first generation of social funds, which were introduced in Latin America. It also does not discuss the effect of social fund investments on capacity building-a more recent emphasis of social funds seeking to assist decentralization and community development.